Antropologia (John Paul II Catholic University of Lublin, Faculty of Philosophy., 2010)
Antropologia [Anthropology] is a gateway to the series of volumes devoted to particular disciplines of philosophy, taking into account their relationship with the Christian worldview and recognizing the need to include the philosophical and ideological diversity of contemporary culture. Antropologia covers Thomist tradition, enriching its achievements with other perspectives, especially Karol Wojtyla's personalism. Increasing influence of "third culture thinking", where the humanities are carried out in the context of the natural sciences, justifies the need to take up the difficult task of demonstrating complex problems of philosophical and natural anthropology. Anthropological considerations force us to realize the multifaceted nature of classical discussions on the nature of man, including theirs scientific and ideological facets, and to demonstrate them in a well-balanced manner. In this context, it enables readers to gain guidance in the debate on the philosophy of mind, providing ways of understanding and assessing the problem of the human soul (concerning the mind-body problem).